HSP27 expression levels are associated with the sensitivity of hepatocellular carcinoma cells to 17-allylamino-17-demethoxygeldanamycin. (March 2013) - Cui, Yuehong; Wu, Weizhong; Zhou, Yuhong; Xie, Qian; Liu, Tianshu; Jin, Jianjun; Liu, Kangda
Aims, materials & methods: As heat-shock proteins are associated with tumor proliferation, differentiation, invasion and metastasis, we investigated whether targeting Hsp90 with the geldanamycin derivative 17-allylamino-17-demethoxygeldanamycin (17AAG) can inhibit the viability of hepatocellular carcinoma cell lines with various levels of metastatic potential. In addition, we investigated whether the use of Hsp27–siRNA can decrease resistance to 17AAG.Results: Although 17AAG upregulated the expression of heat-shock proteins, it did not affect the expression of Hsp90 client proteins in normal hepatocytes. Hsp90 inhibition by 17AAG degraded its client proteins in both low- and high-metastatic potential cell lines. siRNA inhibited Hsp27 expression in cell lines and improved the sensitivity of 17AAG.Conclusion: 17AAG inhibited the viability of hepatocellular carcinoma cells by degrading Hsp90 client proteins. The sensitivity of cells to 17AAG is associated with the level of Hsp27 expression.